Can relaxation exercises improve students’ OSCE grades: A prospective study - Massalou, Damien; Doyen, Jérôme; Almairac, Fabien; Rohrlich, Pierre-Simon; Fournier, Jean-Paul; Vandersteen, Clair; Sadaghianloo, Nirvana (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Introduction: OSCE (Objective Structured Clinical Examination) are a means of assessing health profession students. However, they are a source of stress or anxiety for students. The aim of our study was to improve medical students’ performance during OSCEs by using human performance optimization techniques (HPOT).Methods: Naïve students for OSCE were divided into blocks of five, randomized to HPOT and control groups. Before starting their OSCE circuit, HPOT blocks underwent a 30-minute preparation session. Anxiety was assessed before and after the OSCE using a Visual Analogic Scale (VAS).Results: We randomized and assigned 206 students to 41 blocks of which 20 were HPOT and 21 were control. Anxiety before the exam was significantly reduced thanks to the HPOT procedure with a median value of six and four on the VAS respectively before and after the relaxation session (p = 0.001). The final exam score was not associated with pre-OSCE anxiety (p = 0.5). The HPOT procedure did not improve the final score (p = 0.4). Interestingly, the final score was inversely correlated with the final median anxiety VAS reading after the exam (p = 0.01): students with the lowest anxiety VAS achieved better scores.Conclusion: Relaxation, conscious breathing, and positive reinforcement methods reduced students’ anxiety prior to their OSCE; however, these techniques did not improve their scores.